PERANCANGAN PEMBANGKIT LISTRIK TENAGA SURYA ATAP DI HOTEL NOVOTEL UBUD RESORT & SUITE BALI - I Wayan Arta Saputra; I Nyoman Setiawan; Wayan Gede Ariastina (Jurnal SPEKTRUM, 2021)
The service quality of a hotel is supported by a sustainable supply of electrical energy.Electrical energy at the Novotel Ubud Resort & Suite Bali hotel is supplied from PT. PLN.Source Power plant PT. PLN predominantly uses fossil fuels that are less environmentallyfriendly. The solution to this problem is to use renewable fuels to reduce environmental pollutionand as a source of electrical energy at the Novotel Ubud Resort & Suite Bali hotel. This studyaims to design a rooftop solar power plant at the Novotel Hotel Ubud Resort & Suite Bali. Theresults of the simulation of PLTS electrical energy production using the HOMER application.The feasibility of rooftop solar power plants using the NPV, PI and DPP methods. Based on thedata obtained, the Novotel Ubud Resort & Suite Bali Hotel consists of five flat and pyramidroofedbuildings with a total roof area of 2723 m2. This study uses 576 solar modules with atotal power output of 236.16 kWp and uses 3 inverters with a capacity of 80 kW. The results ofthe HOMER simulation show that the annual electrical energy production from PLTS is 377,083kWh. From the feasibility of PLTS has an NPV value of Rp. 633,125,923, the PI value is 1.25and the DPP value is 13.8 years. The results of this design can be said to be feasible becausethe NPV value is positive and is able to reverse the initial cost of PLTS for 13.8 years from theassumption for 25 years.